2017
DOI: 10.1098/rsos.170920
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic and electrical properties of a new double-perovskite LaNaMnMoO 6 material

Abstract: Structural, magnetic, magnetocaloric, electrical and magnetoresistance properties of an LaNaMnMoO6 powder sample have been investigated by X-ray diffraction (XRD), magnetic and electrical measurements. Our sample has been synthesized using the ceramic method. Rietveld refinements of the XRD patterns show that our sample is single phase and it crystallizes in the orthorhombic structure with Pnma space group. Magnetization versus temperature in a magnetic applied field of 0.05 T shows that our sample exhibits a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…These values verify that the compounds are a cubic symmetry. The Goldschmidt tolerance factor is defined as [23]: (1) Where is the average ionic radius at the A-site of the ABO 3 type compound, and are the ionic radii of the B-site.The ionic radii used for the calculating tolerence factor are Ba 2+ = 1.61 Å, La 3+ = 1.36 Å, Rb 1+ =1.72 Å, Te 6+ = 0.56 Å and O 2-= 1.35 Å [24]. The observed XRD pattern and obtained lattice parameters are very much similar and consistent with the reported ones [22].…”
Section: Amentioning
confidence: 99%
See 1 more Smart Citation
“…These values verify that the compounds are a cubic symmetry. The Goldschmidt tolerance factor is defined as [23]: (1) Where is the average ionic radius at the A-site of the ABO 3 type compound, and are the ionic radii of the B-site.The ionic radii used for the calculating tolerence factor are Ba 2+ = 1.61 Å, La 3+ = 1.36 Å, Rb 1+ =1.72 Å, Te 6+ = 0.56 Å and O 2-= 1.35 Å [24]. The observed XRD pattern and obtained lattice parameters are very much similar and consistent with the reported ones [22].…”
Section: Amentioning
confidence: 99%
“…Double perovskite compounds with the general chemical formula AA'BB'O6, where A, A' are alkali or rare-earth metals and B, B' are transition metals have been extensively studied in recent years [1], [2]. These compounds are important as they exhibit remarkable structural and physical properties which the most significant for the applications in spintronics applications, magnetoresistive and magneto-electric devices [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Reported research findings on doped materials have shown profound results regarding band gap energy, magnetic properties, electrical behavior, etc. [ 16 , 17 , 18 ], which may widen their applications. Thus, substitutional doping is a longstanding method that has been used to modify the characteristics of the materials without changing the crystal structure as the parent material.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite compounds, ABO 3 (where A = cation of alkali, alkaline earth, or lanthanide metal and B = cation of transition metal), have unique chemical and physical properties such as oxidative, magnetic, conductive, refractive, luminescent, and catalytic. With such interesting and valuable characteristics, these compounds have been utilized tremendously in electronic devices as a tuner of the dielectric/ferroelectric responses [7] and an overcomer inefficiency on photovoltaics and other optoelectronic devices [8], sensors as a hydrazine detector [9] and ozone sensing property [10], magnetisms as a huge magnetoresistance [11] and a magnetoelectric response [12], photoluminescences as a highly photoluminescent thin film [13] and a light-emitting material [14], catalysts as CO2/H2 converter into alcohol [15] and pollutant decomposer [16], solid oxide fuel cells as a self-anode in the next power generator [17] and a good performance cathode [18], and photocatalysts as a photo-oxidator of benzylic alcohol [19] and a decomposer of dyes [20].…”
Section: General Introduction Of Lacromentioning
confidence: 99%